Veterinary science and the roel of indonesian veterianarian in national development - Sjarifudin Baharsjah (Hemera Zoa, 1988)
The available of livestock has had profound influences on the growth of civilization. Systematic animal breeding, increasing control over animal diseases., advanced study on nutrition, improvement in food processing, storage and transportation have been great advantages in livestock raising and the use of animal products. In the world as a whole the need for food has grown faster than the supply of deomestic animals. This is a challenge for the veterinary profession. Veterinary science is the science dealing with the prevention control and treatment of domestic animal disesases. There are 5 Faculties of Veterinary Medicine in Indonesia. The number of Indonesian veterinarian is now about 2.000. In dealing with the improvement of livestock production, veterinarians are working closely together with the animal husbandry graduates, a profession produced by the “Facylty of Animal Husbandry” since the late sixties.